2015
DOI: 10.1111/jcmm.12612
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumour activity of RAF265 and ZSTK474 on human TT medullary thyroid cancer cells

Abstract: Medullary thyroid cancer (MTC) is an aggressive malignancy responsible for up to 14% of all thyroid cancer-related deaths. It is characterized by point mutations in the rearranged during transfection (RET) proto-oncogene. The activated RET kinase is known to signal via extracellular signal regulated kinase (ERK) and phosphoinositide 3-kinase (PI3K), leading to enhanced proliferation and resistance to apoptosis. In the present work, we have investigated the effect of two serine/threonine-protein kinase B-Raf (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…It is possible that VEGFR2 targeting contributed to in vivo tumor growth inhibition, similarly to all other effective RET inhibitors. More recently, another group explored synergistic inhibition of RET-mediated signaling and cell growth by the combination of RAF265 with a different PI3K inhibitor, named ZSTK474 (Bertazza et al 2015). ERK and AKT activation, cell growth and survival, and calcitonin expression and secretion were all significantly better inhibited by the combination compared to single treatments, in TT cells.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…It is possible that VEGFR2 targeting contributed to in vivo tumor growth inhibition, similarly to all other effective RET inhibitors. More recently, another group explored synergistic inhibition of RET-mediated signaling and cell growth by the combination of RAF265 with a different PI3K inhibitor, named ZSTK474 (Bertazza et al 2015). ERK and AKT activation, cell growth and survival, and calcitonin expression and secretion were all significantly better inhibited by the combination compared to single treatments, in TT cells.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Several groups have reported the action of RAF inhibitor against VEGFR2 in thyroid cancer. 30,31 Interestingly, in this study, BRAF wild PTCs in cluster 2 showed higher VEGFR2 protein than BRAF V600E PTCs (see Figure 5). Subsequently, we tried to select genes that were differentially expressed between PTCs in cluster 1 and BRAF wild PTCs in cluster 2 (see Figure 6).…”
Section: Discussionmentioning
confidence: 48%
“…In the RPPA analysis, the VEGFR2 protein expression in BRAF wild PTCs of cluster 2 was higher than that in BRAF wild PTCs of cluster 1 (see Figure ). Several groups have reported the action of RAF inhibitor against VEGFR2 in thyroid cancer . Interestingly, in this study, BRAF wild PTCs in cluster 2 showed higher VEGFR2 protein than BRAF V600E PTCs (see Figure ).…”
Section: Discussionmentioning
confidence: 52%
“…With the capacity of the molecule to target RET mutation, the potential of RAF265 to effectively treat the MTC form is important. In this context, combined with the PI3K inhibitor ZSTK474, RAF265 induced a strong cytotoxic effect and a strong inhibition of VEGFR-2 phosphorylation in TT cells harboring genetic alterations in RET [72].…”
Section: Combination To Pi3k Inhibitormentioning
confidence: 97%